Spatio-temporal analysis of sheep and goat pox outbreaks in Uganda during 2011–2022 - Nizeyimana, Gerald; Vudriko, Patrick; Erume, Joseph; Mubiru, Frank; Eneku, Wilfred; Biryomumaisho, Savino; Mwebe, Robert; Arinaitwe, Eugene; Rose, Ademun; Atim, Stella; Ayebazibwe, Chrisostom; Muhanguzi, Dennis; et al. (BMC Veterinary Research, 2023)
Background Sheep and goat pox (SGP) caused by sheep poxvirus (SPV) and goat poxvirus (GPV) respectively; are transboundary and World Organisation for Animal Health (WOAH)-notifiable viral diseases. There is barely any coherent information about the distribution and prevalence of SGP for Uganda. We therefore conducted this study to describe the temporal and spatial distribution of SGP suspected outbreaks in Uganda for the period 2011–2020 as well as serologically confirm presence of SGP antibodies in suspected SGP outbreaks reported in 2021–2022. Results Thirty-seven [37] SGP outbreaks were reported across the country during the study period. North-eastern region [that comprises of Karamoja region] had the highest number of outbreaks [n = 17, 45%]; followed by Central [n = 9, 2.4%], Northern [n = 8, 2.2%] and Western region [n = 3, 0.08%]. Reports from district veterinary personnel indicate that the prevalence of; and mortality rate and case fatality rate associated with SGP were 0.06%, 0.02% and 32% respectively. There was a steady increase in the number of reported SGP outbreaks [x̄ = 4] over the study period. Seropositivity of SGPV antibodies in outbreak sheep and goats that were investigated during the study period [2021–2022] was [n = 41, 27%, 95 CI;] Conclusion Our analyses of SGPV passive and active reports indicate that SGP is present in Uganda with a decade long average of four outbreaks per annum. During this period, about a third of all SGPV-clinically infected animals died. SPG is therefore a major constraint to small ruminant health and productivity in Uganda. Introduction of animals from infected herds and breach in farm biosecurity were the most important predictors of SGP outbreaks. In addition to the already existing SGP commercial vaccines, small ruminant screening for SGPV before introducing them to naïve herds and ensuring on farm biosecurity should be part of the SGP control tool pack for Ugandan small ruminant farmers.